2014
DOI: 10.1098/rspb.2013.2433
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary stasis and lability in thermal physiology in a group of tropical lizards

Abstract: Understanding how quickly physiological traits evolve is a topic of great interest, particularly in the context of how organisms can adapt in response to climate warming. Adjustment to novel thermal habitats may occur either through behavioural adjustments, physiological adaptation or both. Here, we test whether rates of evolution differ among physiological traits in the cybotoids, a clade of tropical Anolis lizards distributed in markedly different thermal environments on the Caribbean island of Hispaniola. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(234 citation statements)
references
References 79 publications
(104 reference statements)
4
218
0
1
Order By: Relevance
“…As a result, behavioural thermoregulation is less effective at reducing variability in the minimum temperatures experienced and in preventing exposure to extreme cold. This mechanism may also contribute to parallel geographical patterns seen in inherent thermal tolerances, where CT min changes more quickly with latitude and elevation than CT max [37,50,51]. The higher thermal plasticity of organisms in aquatic versus terrestrial habitats was unexpected (figures 1 and 3; but see [38]).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, behavioural thermoregulation is less effective at reducing variability in the minimum temperatures experienced and in preventing exposure to extreme cold. This mechanism may also contribute to parallel geographical patterns seen in inherent thermal tolerances, where CT min changes more quickly with latitude and elevation than CT max [37,50,51]. The higher thermal plasticity of organisms in aquatic versus terrestrial habitats was unexpected (figures 1 and 3; but see [38]).…”
Section: Discussionmentioning
confidence: 98%
“…For this study, we focus on body size divergence within two deeply divergent clades from Cuba and Hispaniola. On these islands, lizards are found in environments ranging from scrubby semidesert to montane pine forests, which pose different selective pressures (Glor et al 2003;Muñoz et al 2014a) and provide the opportunity for body size adaptation. By comparing the intra-and interspecific contributions to body size on both of these islands, we test whether size clines are replicated across independent but ecologically convergent clades of Anolis lizards in similar thermal environments.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous work has demonstrated that montane lizards in the Hispaniolan cybotes clade thermoregulate during the day at temperatures comparable to those for their lowland counterparts (Hertz and Huey 1981;Muñoz et al 2014a). Low thermal inertia may aid this thermoregulatory behavior of smaller montane lizards.…”
mentioning
confidence: 99%
“…Very low environmental temperature, relative to the preferred and/or critical temperature of individuals would decrease the available time needed for organisms to effectively basking and thermoregulate. Thus, lizards from highland environments could face the effects of low temperatures using two strategies as extremes of a continuum: by behavioral adjustments, such as searching more exposed and sunny microsites and reducing activity time (Hertz & Huey, 1981;Hertz, 1981;Gvoždík & Castilla, 2001;Gvoždík, 2002) or by physiological adaptation, such as decreased in the critical temperature minimum values to hold out cold environments (Muñoz et al, 2014). Besides, based on data about thermal biology, Sinervo et al (2010) hypothesized that high elevation reptile species are particularly threatened by climate change, due to their restricted distribution, which would decrease progressively as temperature increase, and as these environments are colonized by competitors or predators from lowlands, pushing up highland species toward an "endless road", at higher elevations.…”
Section: Palabras-clavementioning
confidence: 99%
“…Species of this genus has been used as model organisms to design a methodology to characterize thermoregulatory strategy in reptiles (Hertz et al, 1993); a protocol widely used since then (Díaz & Cabezas-Díaz, 2004;Blouin-Demers & Nadeau, 2005;Hitchcock & McBrayer, 2006;Row & BlouinDemers, 2006;Herczeg et al, 2008). Studies on Anolis have showed that thermoregulatory strategy varies among species, elevations and seasons, revealing high behavioral and physiological plasticity for dealing with the challenges imposed by the environment (Huey & Webster, 1975;Hertz & Huey, 1981;Hertz, 1981;Hertz et al, 1993;Muñoz et al, 2014).…”
Section: Palabras-clavementioning
confidence: 99%